Prognostic factors in uterine adenosarcoma: subanalysis of the SARCUT study - Mancari, Rosanna; Yusuf, Yildirim; Macuks, Ronalds; Achimas-Cadariu, Patriciu; Piek, Jurgen Martinus; Sperduti, Isabella; Corrado, Giacomo; Vizza, Enrico; Zapardiel, Ignacio (Frontiers in Oncology, 2024)
Objective The purpose of the study was to analyse the role of prognostic factors on the risk of recurrence and overall survival of patients with uterine adenosarcoma. Methods A retrospective international multicentre study involving 46 centres collected 32 cases of uterine adenosarcoma, and these cases were included in the present subanalysis. Clinical and demographic features and tumour characteristics were gathered, as well as information on treatment and relapse. Disease-free and overall survival were analysed. Results The 5-year disease-free survival (DFS) was 85.3% and the 5-year overall survival (OS) rate was 89.5%. The risk factors significantly associated with overall survival were age (HR 1.09, 95% CI 1.03–1.15; p = 0.004) and FIGO stage II–III (HR 17.75, 95% CI 2.87–109.93; p = 0.002). Patients who experienced early relapse (within 12 months) had a tumour size >30 mm and advanced stage. The majority of recurred cases were treated with radiotherapy or surgery and obtained a good response rate. Conclusion The most significant prognostic factors in uterine adenosarcoma were age and FIGO stage and, indirectly, tumour size at diagnosis. The use of secondary surgery and/or radiotherapy could help in prolonging the disease-free status of the patients.